ANALISIS NILAI TAMBAH PENGOLAHAN IKAN MUJAIR MENJADI IKAN ASIN DI DESA WEDUNI KECAMATAN DEKET KABUPATEN LAMONGAN - Wachidatus Sa'adah (Universitas Galuh Ciamis, 2021)
The processing is carried out so that the fish and fishery products have added value. The purpose of fish processing is to reduce the water content in the fish body, one way is by making salted fish. The fish that are usually processed into salted fish in Deket District are freshwater fish, namely tilapia fish. The choice of tilapia fish because it is in fresh condition, the price is cheap and if it has been processed into salted fish, it taste good and is very attractive to the community. The purpose of this research was to determine the added value of processing tilapia fish into salted in Weduni Village, Deket District, Lamongan Regency. The method used in this research is quantitative method, and the sampling is done by purposive sample in the fishery product processing group, the name of group is “Dhie RT Dagelan”. The results showed that the added value obtained was Rp. 50.505/kg with a value added ratio of 70,14%